Exploring two tumor treatment strategies: effectiveness of ribosome inactivating proteins and mesenchymal stem cells/MSC derived extracellular vesicles in cancer treatment - Mavaei, Maryamosadat; Farokhi, Simin; Yousefi, Mohammad Hasan; Fakouri, Arshia; Shadab, Alireza; Abdolmohammadi, Mohammad Hossein; Fallahian, Faranak; Afkhami, Hamed (Frontiers in Oncology, 2025)
Cancer is a complex and heterogeneous disease that often requires multifaceted treatment strategies to achieve optimal therapeutic outcomes. Given the limitations of single-agent therapies, particularly in the face of intricate biological signaling networks and treatment resistance, there is a growing need for combinatory approaches. This article presents a novel hypothesis: the simultaneous use of ribosome-inactivating proteins (RIPs) and mesenchymal stem cells (MSCs) or MSC-derived extracellular vesicles (EVs) in cancer treatment. RIPs, with their potent cytotoxic properties, can target tumor cells effectively, while MSCs, known for their tumor-homing abilities and regenerative potential, can serve as delivery vehicles, potentially enhancing the targeting precision and reducing the systemic toxicity of RIPs. This hypothesis explores the synergistic potential of combining these two therapeutic modalities, leveraging the advantages of both techniques to create a more effective cancer treatment strategy. By combining RIPs’ ability to inhibit protein synthesis with MSCs or MSC-derived EVs’ capability to modulate the tumor microenvironment and deliver therapeutic agents. This approach offers a promising avenue for overcoming cancer’s inherent complexity. However, challenges remain, such as optimizing dosing protocols, addressing safety concerns, and ensuring efficient drug delivery. Future research and clinical trials are necessary to validate this combination as a viable cancer therapy.